ANALISIS KESIAPAN UPT PUSKESMAS LOTU MENGHADAPI AKREDITASI PUSKESMAS - Iradat Zega; R. Kintoko Richadi; Frida Lina Tarigan; Donal Nababan; Mido Ester J. Sitorus; Sonny Priajaya Warouw (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2022)
The Community Health Center is a functional organization that organizes health efforts that are comprehensive, integrated, equitable, acceptable and affordable to the community. These health efforts are carried out with an emphasis on shipping by prioritizing promotive and preventive efforts to achieve the highest public health status in the working area. To ensure the quality of health services, puskesmas are required to be accredited. In North Nias Regency, one of the UPT Puskesmas must be accredited to improve the quality of services in the community. To carry out this accreditation, puskesmas are required to make preparations before accreditation. The research carried out is a qualitative research with the aim of providing a comprehensive, broad and in-depth picture of the readiness of the Lotu Health Center UPT to Face Lotu Health Center Accreditation. The data were collected by means of in-depth interviews and also by making observations. Furthermore, the data will be analyzed by researchers to make it easier to see the complete data. The results showed that the UPT Puskesmas Lotu was still not ready for accreditation. This is due to the incomplete requirements provided for accreditation such as the unpreparedness of puskesmas accreditation documents due to the Covid-19 pandemic, inadequate infrastructure such as laboratory equipment, dental examination kits. And seen from the human resources owned by the UPT Puskesmas Lotu, there are still a lot of shortcomings such as pharmacy staff, laboratory personnel, physiotherapy, and even general practitioners. Based on the results of the research, it is hoped that the UPT Puskesmas Lotu will immediately prepare for existing deficiencies such as completing accreditation documents, lacking facilities and infrastructure, preparing human resources, and increasing team cooperation so that preparations can be made more optimal. Coordination between the UPT Puskesmas Lotu and the North Nias Regency Health Office should be improved, especially in disbursing the accreditation budget.